Laminoplasty versus laminectomy and fusion for multilevel cervical compressive myelopathy: A meta-analysis. Issue 23 (June 2016) - Liu, Feng-Yu; Yang, Si-Dong; Huo, Li-Shuang; Wang, Tao; Yang, Da-Long; Ding, Wen-Yuan
Abstract : Abstract: This is a meta-analysis to compare the results between laminoplasty and laminectomy followed by fusion for the patients with multilevel cervical compressive myelopathy. An extensive search of literature was performed in MEDLINE, Embase, the Cochrane library, CNKI, and WANFANG. The following outcome measures were extracted: the Japanese Orthopaedic Association (JOA) scores, cervical curvature index (CCI), visual analog scale (VAS), cervical lordosis (C2–7), complications, blood loss, and operation time. Data analysis was conducted with RevMan 5.3 and STATA 12.0. A total of 23 studies comprising 774 and 743 patients treated with laminoplasty and laminectomy followed by fusion, respectively, were included in the final analysis. The pooled analysis showed that there was no significant difference in preoperative JOA scores [ P = 0.89], postoperative JOA scores [ P = 0.13], JOA scores improvement rate [ P = 0.27], preoperative CCI [ P = 0.15], postoperative CCI [ P = 0.14], preoperative VAS [ P = 0.41], postoperative VAS [ P = 0.52], preoperative cervical lordosis (C2–7) [ P = 0.46], postoperative cervical lordosis (C2–7) [ P = 0.67], total complications [ P = 0.07], axial pain [ P = 0.94], and blood loss [ P = 0.51]. However, there were significant difference in operation time (WMD = −19.57 [−32.11, −7.02], P = 0.002) and C5 palsy (OR = 0.26 [0.15, 0.44], P  < 0.001). As compared with laminectomy followed by fusion, expansive laminoplasty showed no significant differences in JOA scores, CCI, ROM, VAS, cervical lordosis (C2–7), axial pain, total complications, and blood loss, but shorter operation time and fewer C5 palsy.